Nitrogen and wastewater: origins, effects and removal mechanisms to preserve the environtment and public health - Cardenas Calvachi, Gloria Lucia; Sanchez Ortiz, Ivan Andrés (Universidad y Salud, 2013)
Introduction: The wastewater treatment, traditionally based on removal of solids, oathogens and organic matter, have focused specially on nutrient removal, mainly of nitrogen due to the environmental and sanitary consequences of its presence on water resources such increased acidity, eutrophication and toxicity of aquatic ecosystems, that affect the survival, growing and reproductive capacity of some animals. Certain forms of nitrogen on water establish risks for humans througth its ingestion or direct contact with compounds as toxins released by cyanobacteria blooms on eutrophic envirinments. Methods: This reviw deals with the forms of nitrogen compounds on water; their origins and impacts on water resources, some hydro biological species and public health. It also briefly describes the conventional options for nitrogen compounds transformation or removal in wasterwater. The biological elimination alternatives are emphasized because they can completely remove the contaminant and not transfer it to other systems. Results: The presented information is important for the selection of wastewater treatment systems and nitrogen removal of wastewater in order to reduce their impacts on water bodies and preserve the public health.